ANALISIS KEBIJAKAN PEMERINTAH DAERAH DALAM PENGELOLAAN SAMPAH DI KABUPATEN OGAN KOMERING ULU - Fani Syahrani; Rakhmat Saleh; Eva Susanti (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2025)
his study analyzes local government policies on waste management in Ogan Komering Ulu Regency, which have become increasingly complex due to population growth and development activities. Waste management issues are not merely technical problems but also involve environmental political dynamics, public policy, and the roles of various actors. This research aims to examine how environmental political dynamics influence the formulation, legitimacy, and implementation of waste management policies. The research employs a descriptive qualitative method with data collection techniques including interviews, observation, and documentation. Informants consist of officials from the Environmental Agency, academics, waste management practitioners, and community members. The findings indicate that the Environmental Agency plays a central role in waste management; however, policy implementation has not been optimal due to limited facilities, low public awareness, and weak coordination among stakeholders. Effective waste management requires strong synergy between local government, the local parliament, the community, and non-governmental actors. Strengthening environmental politics through increased community participation, institutional reinforcement, and consistent local policies is essential for achieving sustainable waste management.